Interobserver variation in classifying lymphomas among hematopathologists - Tawatchai Pongpruttipan (2018)
© 2014 Pongpruttipan et al. Background: Lymphomas are common malignancies that have various subtypes with many overlapping histologic, immunophenotypic and genetic features. Therefore, discordance in classifying lymphoma among pathologists may be encountered. But this issue is not well characterized. We conducted the present study to demonstrate discordances among Thai hematopathologists as well as to highlight common arguing points for classifying lymphomas.Methods: The 117 lymphoma cases were randomly retrieved and individually reviewed by 7 hematopathologists, members of the " Thai Hematopathologist Group," without knowing the original diagnoses. The consensus diagnoses were given from a discussion by all members. In each case, the diagnosis from each participant was compared with the consensus diagnosis and classified into 4 categories as follow: 1) concordance, 2) minor discordance, 3) major discordance and 4) serious discordance.Results: There were approximately 11% discordances between original and consensus diagnoses. The average discordances among all pathologists according to minor, major and serious discordances were 10%, 3.5% and 0.3%, respectively. Diffuse large B-cell lymphoma had the least discordance (7%). Small biopsies had been found to increase discordances in some lymphoma subtypes.Conclusions: The present study reveals some degrees of interobserver variation in classifying of lymphoma by using the 2008 WHO classification among hematopathologists. Some types of lymphomas on small biopsies were found to have a significant higher discordance rate. This study also described some common diagnostic discordances regarded as potential pitfalls in classifying lymphomas.